Long-term outcome of the survivors of infantile hypercalcaemia with CYP24A1 and SLC34A1 mutations - Janiec, Agnieszka (Nephrol Dial Transplant, 2020)
BACKGROUND: Infantile hypercalcaemia (IH) is a vitamin D(3) metabolism disorder. The molecular basis for IH is biallelic mutations in the CYP24A1 or SLC34A1 gene. These changes lead to catabolism disorders (CYP24A1 mutations) or excessive generation of 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] (SLC34A1 mutations). The incidence rate of IH in children and the risk level for developing end-stage renal disease (ESRD) are still unknown. The aim of this study was to analyse the long-term outcome of adolescents and young adults who suffered from IH in infancy. DESIGN: Forty-two children (23 girls; average age 10.7 ± 6.3 years) and 26 adults (14 women; average age 24.2 ± 4.4 years) with a personal history of hypercalcaemia with elevated 1,25(OH)(2)D(3) levels were included in the analysis. In all patients, a genetic analysis of possible IH mutations was conducted, as well as laboratory tests and renal ultrasonography. RESULTS: IH was confirmed in 20 studied patients (10 females). CYP24A1 mutations were found in 16 patients (8 females) and SLC34A1 in 4 patients (2 females). The long-term outcome was assessed in 18 patients with an average age of 23.8 years (age range 2–34). The average glomerular filtration rate (GFR) was 72 mL/min/1.73 m(2) (range 15–105). Two patients with a CYP24A1 mutation developed ESRD and underwent renal transplantation. A GFR <90 mL/min/1.73 m(2) was found in 14 patients (77%), whereas a GFR <60 mL/min/1.73 m(2) was seen in 5 patients (28%), including 2 adults after renal transplantation. Three of 18 patients still had serum calcium levels >2.6 mmol/L. A renal ultrasound revealed nephrocalcinosis in 16 of 18 (88%) patients, however, mild hypercalciuria was detected in only one subject. CONCLUSIONS: Subjects who suffered from IH have a greater risk of progressive chronic kidney disease and nephrocalcinosis. This indicates that all survivors of IH should be closely monitored, with early implementation of preventive measures, e.g. inhibition of active metabolites of vitamin D(3) synthesis.